2022
DOI: 10.3390/socsci11090423
|View full text |Cite
|
Sign up to set email alerts
|

Employee Involvement and Commitment in Internal Communication

Abstract: This research project aims to analyze the importance of internal communication in organizations in Benguela (Angola) and to determine its impact on employee engagement and commitment to the organization. To this end, an exploratory study was conducted using a quantitative methodology. In this scope, a questionnaire was applied to 250 employees of the organizations, seeking to evaluate employees as internal consumers; internal communication in terms of tools, means and communicative effectiveness, as well as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
5
0
2
Order By: Relevance
“…This is particularly relevant in light of the ongoing reflection on specific variables arising from the isolation brought about by the Covid-19 pandemic, which has impacted organizational relationships and communication within and between organizations. Additionally, our study aligns with the findings ofMeirinhos et al (2022), illustrating the vital role of communication in fostering organizational cohesion for entities seeking to enhance their performance.A number of findings which emerged from the testing stood out on account of the strong scientific evidence they put forward based on the methodological protocols and the theoretical framework. The findings primarily evidenced that communication with the immediate supervisor is a factor of great significance within the internal communication process.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…This is particularly relevant in light of the ongoing reflection on specific variables arising from the isolation brought about by the Covid-19 pandemic, which has impacted organizational relationships and communication within and between organizations. Additionally, our study aligns with the findings ofMeirinhos et al (2022), illustrating the vital role of communication in fostering organizational cohesion for entities seeking to enhance their performance.A number of findings which emerged from the testing stood out on account of the strong scientific evidence they put forward based on the methodological protocols and the theoretical framework. The findings primarily evidenced that communication with the immediate supervisor is a factor of great significance within the internal communication process.…”
supporting
confidence: 87%
“…Togna (2014) found that trust in the Italian company he studied is at the center of the triadic relationship between communication, trust, and commitment, and that faceto-face communication is essential for moving from the stage of trust to the stage of commitment. Meirinhos et al (2022) conducted a study in Angola and concluded that internal communication is a necessary management tool for any organization that seeks to increase its performance. Thus, we can appreciate that effective internal communication can help to build trust, create a sense of community, and ensure that employees are aligned with the organization's goals.…”
Section: Aiming To Keepmentioning
confidence: 99%
“…Involving employees enhances the meaningfulness of work (Frega, 2021). It empowers people to unravel management issues (Lasrado et al, 2016), design actions intended to improve individual and collective performance (Pasmore and Friedlander, 1982), and assess the implications of organizational dynamics on work-related wellbeing (Meirinhos et al, 2022). EI is especially fitting to cope with concerns that affect individual work conditions (Adler et al, 1997).…”
Section: The Imperfections Of Employee Involvementmentioning
confidence: 99%
“…It is also important to emphasise the provision of a pleasant working environment (Slijepčević et al , 2018), as this may be the factor that facilitates the most significant retention of the knowledge that is transmitted. Because of this, the IC of an organisation is essential (Meirinhos et al , 2022), as it contributes to the development of competitiveness (Sušanj Šulentić, 2014) and raises the level of employee productivity (Chmielecki, 2015; Slijepčević et al , 2018; Chen, 2020; Titisari et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of studies, on the contrary, study how IC affects the levels of engagement, motivation and satisfaction experienced by workers (Mishra et al , 2019; Santiago, 2020; Meirinhos et al , 2022). However, few studies have examined how IC affects employees’ loyalty or commitment.…”
Section: Introductionmentioning
confidence: 99%